2010
DOI: 10.1590/s1984-46702010000600001
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Ucides cordatus (Decapoda: Ocypodidae) megalopae during transport under different conditions of density and duration

Abstract: Target areas for Ucides cordatus (Linnaeus, 1763) restocking programs are often located far from the laboratory where larval rearing is developed. During translocation, the larvae are submitted to highly stressful conditions due to handling, packing, and transport activities. The aim of the present study was to assess the mortality rates of U. cordatus megalopae caused by different transportation procedures. Megalopae at loading densities of 50, 150, and 300 ind.L-1 were packed in double polyethylene 12 x 25 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Smith and Ribelin (1984) concluded that post-larvae of the shrimp Litopenaeus vannamei (Boone, 1931) can be transported for up to 18 hours at a density of 190 ind.L with insignificant mortality. Additionally, Ventura et al (2010) investigated the survival of Ucides cordatus Linnaeus, 1763 (Decapoda: Ocypodidae megalopae) and concluded that they can be transported at loading densities of 300 ind.L -1 during periods of six hours with minimal mortality. Only one of the reviewed studies reported lower survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Smith and Ribelin (1984) concluded that post-larvae of the shrimp Litopenaeus vannamei (Boone, 1931) can be transported for up to 18 hours at a density of 190 ind.L with insignificant mortality. Additionally, Ventura et al (2010) investigated the survival of Ucides cordatus Linnaeus, 1763 (Decapoda: Ocypodidae megalopae) and concluded that they can be transported at loading densities of 300 ind.L -1 during periods of six hours with minimal mortality. Only one of the reviewed studies reported lower survival rates.…”
Section: Discussionmentioning
confidence: 99%